ANALYSIS OF OCCUPATIONAL DERMATOSIS MORBIDITY IN IRKUTSK REGION - O. V. Ushakova (Acta Biomedica Scientifica, 2012)
The results of the analysis of the incidence of professional dermatosis in the Irkutsk region for the period, from 2006 to 2010. The features of the clinical course of disease of the skin and the most important etiological factors in various occupational groups. Prevalence of allergic occupational structure in the skin lesions. Analysis of the frequency distribution, of the surveyed, persons by industry allowed, to ascertain the highest prevalence of allergic diseases among health, care workers — 46, 2%. In the chemical industry, the formation of pathological skin against toxic lesions of the respiratory system., in mechanical engineering and. metallurgy — the tendency to torpid, course of skin process.